Diagnosing Hirschsprung Disease in Children Younger than 6 Months of Age: Insights in Incidence of Complications of Rectal Suction Biopsy and Other Final Diagnoses - Beltman, Lieke; Labib, Hosnieya; Masselink, Marit; Backes, Manouk; Benninga, Marc A.; Roelofs, Joris J.T.H.; van der Voorn, J. Patrick; van Schuppen, Joost; Oosterlaan, Jaap; van Heurn, L.W. Ernest; Derikx, Joep P.M. (European Journal of Pediatric Surgery, 2023)
Background The gold standard for diagnosing Hirschsprung disease (HD) in patients younger than 6 months is pathological examination of rectal suction biopsy (RSB). The aim of this study was to gain insight into the following: (1) complications following RSB, (2) final diagnosis of patients referred for RSB, and (3) factors associated with HD.Methods Patients suspected of HD referred for RSB at our center were analyzed retrospectively. Severity of complications of RSB was assessed using Clavien–Dindo (CD) grading. Factors associated with HD were tested using multivariate logistic regression analysis.Results From 2000 to 2021, 371 patients underwent RSB because of infrequent defecation, at a median age of 44 days. Three patients developed ongoing rectal bleeding (0.8%) graded CD1. Most frequent final diagnoses were: HD (n = 151, 40.7%), functional constipation (n = 113, 31%), idiopathic meconium ileus (n = 11, 3%), and food intolerance (n = 11, 3%). Associated factors for HD were male sex (odds ratio [OR], 3.19; confidence interval [CI], 1.56–6.53), presence of syndrome (OR, 7.18; CI, 1.63–31.69), younger age at time of RSB (OR, 0.98; CI, 0.85–0.98), meconium passage for more than 48 hours (OR, 3.15; CI, 1.51–6.56), distended abdomen (OR, 2.09; CI, 1.07–4.07), bilious vomiting (OR, 6.39; CI, 3.28–12.47), and failure to thrive (OR, 8.46; CI, 2.11–34.02) (model R2 = 0.566).Conclusion RSB is a safe procedure with few and only minor complications. In the majority of patients referred for RSB under the age of 6 months, HD was found followed by a functional cause for the defecation problems. RSB should be obtained on a low threshold in all patients under the age of 6 months with the suspicion of HD.
Keywords: Hirschsprung disease; rectal suction biopsy; complications; associated factors; differential diagnosis